Recent Advances in Graphene Research - Kumar Nayak, Pramoda (IntechOpen, 2016)
This book ''Recent Advances in Graphene Research'' provides a state-of-the-art report of the knowledge accumulated in graphene research. It contains 12 chapters divided into three sections. Section 1 ''Fundamentals of Graphene'' deals with quantum hall effect in graphene, electronic properties of carbon nanostructures and spectral statistics of graphene nanoflakes. In Section 2 ''Graphene Synthesis,'' the optimized synthesis procedures of graphene and its derivatives are presented. The application of graphene and its nanostructured-based materials for energy storage, conservation and other extensive applications are described in Section 3 ''Application of Graphene and its Nanostructures''. We believe that this book offers broader prospective to the readers in the recent advances in graphene research, starting from fundamental science to application.